Genetic variation of Anggoli fish (Pristipomoides multidens) based on allozyme patterns - ENDANG WIGATI; SUTARNO SUTARNO; HARYANTI HARYANTI (Biodiversitas Journal of Biological Diversity, 2003)
The objectives of the research were to study the genetic variation and allozyme band pattern of Pristipomoides multidens from several locations of Indonesian sea based on the pattern of allozyme. Samples of the fish were collected from three geographically different water areas of Bali, Sumbawa and Moluccas. Ten different enzymes, ADH, MDH, LDH, α-GPD,PGM, GPI, IDH, ME, EST and SP were used in this study. Polymorphic loci of genetic variation were in line with the Hardy-Weinberg’s equilibrium. The genetic variation was calculated based on the proportion of polymorphic loci, frequency ofallele, amount of allele per locus, and heterozygosity. The results of this research indicate that from the 10 differentenzymes, 16 loci were detected, and 3 of them were polymorphic (PGM-1, GPI-1 and EST). Population of Moluccas has 2 polymorphic loci (PGM-1 and GPI-1) by proportion of 13%, however, population from Bali and Sumbawa has only 1polymorphic locus (EST-1) with the value of 6%. The allelic number per locus was 1.06 – 1.125, while the observedheterozygosity (D) of the populations was 0.005. The fish population of Moluccas is having better genetic variation than that of population from Bali and Sumbawa. The genetic distance between populations was between 0.002 – 0.005. The closestgenetic distance is between Bali and Sumbawa (D = 0,002), while the longest genetic distance was resulted betweenpopulations of Sumbawa and Moluccas (D = 0.005). Based on the UPGMA cluster analysis for the genetic distances,indicated that there was 2 main geographic groups, (1) Moluccas, and (2) Bali and Sumbawa as single population.© 2003 Jurusan Biologi FMIPA UNS SurakartaKey words: allozyme, genetic variation, Pristipomoides multidens.